2007
DOI: 10.1097/nen.0b013e318159886b
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Delivery of Hepatocyte Growth Factor From Amyotrophic Lateral Sclerosis Onset Suppresses Disease Progression in Rat Amyotrophic Lateral Sclerosis Model

Abstract: Hepatocyte growth factor (HGF) is one of the most potent survival-promoting factors for motor neurons. We showed that introduction of the HGF gene into neurons of G93A transgenic mice attenuates motor neuron degeneration and increases the lifespan of these mice. Currently, treatment regimens using recombinant protein are closer to clinical application than gene therapy. To examine its protective effect on motor neurons and therapeutic potential we administered human recombinant HGF (hrHGF) by continuous intrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 32 publications
2
55
0
1
Order By: Relevance
“…The overexpression of mutant human SOD1 in mice is used as a model of ALS. These mutant SOD1 transgenic (Tg) mice reproduce the major phenotypic features of human ALS [7,8], and could be used in analyzing the pathomechanism of ALS [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of mutant human SOD1 in mice is used as a model of ALS. These mutant SOD1 transgenic (Tg) mice reproduce the major phenotypic features of human ALS [7,8], and could be used in analyzing the pathomechanism of ALS [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the mixture of type-1 collagen and b-TCP was expected to provide a biodegradable scaffold for local delivery of HGF. On the other hand, previous studies using local administration of HGF in various models in different species including rabbit revealed significant therapeutic effects of 100 lg HGF [11,[31][32][33][34]. Therefore, we selected a dose of 100 lg HGF/injection for the HGF/b-TCP/collagen complex because HGF was expected to exert biological effects and we could evaluate if HGF would have therapeutic benefits in this rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…In Parkinson's disease HGF gene transfer has 741 been shown to protect dopaminergic neurons from a 6-hydro-742 xydopamine challenge (Koike et al, 2006). In Alzheimer's disease 743 Takeuchi et al (2008) have reported that HGF gene treatment 744 reduced amyloid-b-induced cognitive impairment in mice.745 With amyotrophic lateral sclerosis HGF gene treatment has been 746 shown to delay disease progression in mouse(Sun et al, 2002) 747 and rat models(Ishigaki et al, 2007). The next sections focus 748 on the role of HGF in memory, Alzheimer's and Parkinson's 749 diseases.750 7.5.…”
mentioning
confidence: 98%